Mapping the chaperonin TRiC/CCT interactome in mouse photoreceptors reveals functional significance for energy metabolism - Celine Brooks; David Salcedo-Tacuma; Isabella Mascari; Mark Eminhizer; Tuan Ngo; Douglas Kolson; Emily Sechrest; Tongju Guan; Neil Billington; Wen-Tao Deng; David Smith; Jianhai Du; et al. (PLoS ONE, 2026)
The eukaryotic chaperonin TRiC/CCT is essential for folding a diverse set of proteins, yet its interactome and functional roles in specialized neurons remain incompletely understood. To investigate TRiC-mediated folding in rod photoreceptors, we generated a transgenic mouse line expressing an epitope-tagged Tcp-1α subunit, enabling purification of intact TRiC complexes from retinal tissue. Mass spectrometry identified 226 TRiC-interacting proteins, including known TRiC substrates and co-chaperones as well as numerous novel candidates enriched in RNA processing, cytoskeletal organization, and cell-cycle regulation. Using a TRiC loss-of-function model in which expression of a short splice isoform of phosducin-like protein (PhLPs) competitively inhibits TRiC activity, we observed marked reductions in canonical TRiC substrates, including tubulins, transducin β subunits, and triosephosphate isomerase, as well as secondary alterations in proteins involved in cytoskeletal stability, membrane trafficking, energy metabolism, and phototransduction. Quantitative metabolomic profiling revealed that TRiC deficiency induces a metabolic “energy crisis” characterized by reduced glycolytic- and tricarboxylic acid cycle intermediates, acylcarnitines, ATP, NAD, and NADH, implicating widespread impairment of glucose utilization, mitochondrial bioenergetics, and fatty acid oxidation. Integrative proteomic–metabolomic analysis identified a small subset of proteins, including Rab10 and Anxa1, as potential drivers of these metabolic disruptions, with defective Rab10-dependent GLUT4 trafficking emerging as a plausible mechanism underlying impaired glucose uptake in TRiC-deficient rods. Finally, experiments using a perpetually unfolded Gβ 1 mutant and Gγ 1 -knockout mice demonstrated that substrate overload sequesters TRiC and competitively displaces other clients, exacerbating proteostasis imbalance. Together, our study provides a comprehensive in vivo mapping of the TRiC interactome in mammalian rods, reveals a connection between TRiC-dependent proteostasis and energy metabolism in rods, and indicates a mechanism by which misfolded TRiC substrates exacerbate a proteostasis imbalance that ultimately results in neurodegeneration.